2017
DOI: 10.1016/j.whi.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Women's Preferred Sources for Primary and Mental Health Care: Implications for Reproductive Health Providers

Abstract: Purpose To describe women’s preferences for reproductive health providers as sources of primary and mental health care. Methods Secondary data analysis of the Women’s Health Care Experiences and Preferences Study, an internet survey conducted in September 2013 of 1,078 women aged 18–55 randomly sampled from a U.S. national probability panel. We estimated women’s preferred and usual sources of care (reproductive health providers, generalists, other) for various primary care and mental health care services usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Health care providers are often the primary source of mental health resources and care for women during the perinatal period, 9 indicating a significant role of providers in helping to identify and manage (eg, treat/refer) perinatal mood disorders. 10 , 11 However, a prior study found that maternal depression is assessed in primary care settings less than 50% of the time, and the use of screening tools is even lower (22%-46%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care providers are often the primary source of mental health resources and care for women during the perinatal period, 9 indicating a significant role of providers in helping to identify and manage (eg, treat/refer) perinatal mood disorders. 10 , 11 However, a prior study found that maternal depression is assessed in primary care settings less than 50% of the time, and the use of screening tools is even lower (22%-46%).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Exposure to environmental stressors, such as natural disasters, can amplify perinatal mood disorders and even have intergenerational impacts on child health and development outcomes. [5][6][7][8] Health care providers are often the primary source of mental health resources and care for women during the perinatal period, 9 indicating a significant role of providers in helping to identify and manage (eg, treat/refer) perinatal mood disorders. 10,11 However, a prior study found that maternal depression is assessed in primary care settings less than 50% of the time, and the use of screening tools is even lower (22%-46%).…”
Section: Introductionmentioning
confidence: 99%
“…Obstetrics-Gynecology as Primary Care Setting Many women, especially those of reproductive age, prefer to access primary care through their ob-gyn (Hall et al, 2017;Henderson & Weisman, 2005;Leader & Perales, 1995), and many ob-gyns recognize their role as primary care providers to women (48%; Leader & Perales, 1995). In two recent large studies, 20%-22% of women identified their ob-gyn as their preferred primary care provider (PCP) (Hall et al, 2017;Mazzoni et al, 2017). The percentage nearly doubles among women with lower socioeconomic status: 38% of women in a Medicaid-enrolled sample identified an ob-gyn as their primary provider (Scholle & Kelleher, 2003).…”
Section: Need For Ibh In Ob-gyn Settingsmentioning
confidence: 99%
“… 91 These findings corroborate national survey data of family planning clinicians, which found that of these clinicians, approximately one-third used a validated screening measure and one-fifth provided a referral that consisted of more than a list of treatment options. 92 …”
Section: Barriers and Facilitators To Sbirt Implementationmentioning
confidence: 99%